Between pilgrimage, tourism and liminarity: the search for places - Adam, Júlio Cézar (2018)
This article reflects on the anthropological aspect of the pilgrimage, the human journey, as a metaphor for life, as a way of relating and understanding religion, spirituality, life itself and tourism as forms of pilgrimage.  The pilgrimages of the Christian tradition will be analyzed, seeking to understand them of the anthropology of Victor Turner, analyzing the pilgrimage as a state of liminality and liminoid. Concretely we will look at the case of the Romarias da Terra in Brazil, as an example of liminality/ liminoid and communitas. In addition, this article reflects on the "new centers" of pilgrimage, outside the religious scope, as spaces of pop culture or the visit to tourist sites and monuments of social and cultural memory. The goal is to understand where people have pilgrims and what the meaning of these pilgrimages. In this displacement out of the religious scope, one wonders if tourism would also be a form of pilgrimage. Or would tourism lack precisely the preliminary aspect, something that could be related to Bauman's analysis of the tourist and the vagabond? It is suspected that in a globalized world, places lose their content and identity. People pass through places, but places no longer pass through them. With this, walking also loses its liminal function.